Validation of the pSUAPP Questionnaire and User Experience Evaluation of the Satu Sehat Health Application in Indonesia - Vina Eriyandi; Riki Daniel Tanebeth; Dwiza Riana; Sri Hadianti (SAFE-Network, 2026)
The increasing use of digital health applications in Indonesia requires valid and reliable instruments to evaluate usability and user experience. This study aims to adapt and validate the pSUAPP questionnaire in the Indonesian context and to assess the usability of the Satu Sehat application. A cross-sectional validation study was conducted from May to June 2025 involving 102 active users of the Satu Sehat application, with 90 respondents included in the final psychometric analysis. The adapted pSUAPP questionnaire consists of 27 items covering four domains: first contact, registration, features, and overall user experience. Reliability and validity were assessed using Cronbach’s alpha, correlation analysis with SUS, and exploratory factor analysis (EFA). The results showed that the mean pSUAPP score was 67.76 (SD = 18.39), indicating moderate usability. The registration domain obtained the highest score (mean = 87.50; SD = 12.50), while the feature (mean = 70.36) and experience (mean = 69.62) domains showed relatively lower scores. The questionnaire demonstrated high internal consistency, with strong correlations across domains and with SUS. EFA identified four factors explaining 76.7% of the total variance. No significant differences were observed across sociodemographic characteristics. In conclusion, the Indonesian version of the pSUAPP questionnaire is a valid and reliable instrument for evaluating digital health applications. While the Satu Sehat application performs well in registration, improvements are needed in monitoring features and user experience to support long-term engagement.